RESPON PERTUMBUHAN TANAMAN PAKCOY (Brassica rapa L.) PADA BERBAGAI JENIS MEDIA TUMBUH DALAM SISTEM BUDIDAYA VERTIMINAPONIK - I Nyoman Wahyu Ardianta; I Nyoman Rai; Ni Nyoman Ari Mayadewi (UPN VETERAN JAWA TIMUR, 2021)
Vertiminaponics is a combination of plant cultivation (hydroponics) and fish cultivation (aquaculture) in one place/land arranged vertically. In the vertiminaponic system, the planting medium plays an important role as one of the determinants of plant and fish growth. The purpose of this study was to find the best growing media for pakcoy growth and yield and catfish growth and yield in the vertiminaponic system. This study used a randomized block design (RBD) with one factor, namely the planting medium consisting of four levels, i.e. broken bricks, malang sand, gravel and zeolite. The results showed that the planting medium of malang sand produced the highest total dry weight (12.42 g) and total fresh weight of pakcoy (240.72 g). The zeolite growing media gave the highest weight of catfish in the vertiminaponic system (11.75 kg), but it was not significantly different from malang sand (11.03 kg).